The determinants of academic achievements among students of UiTMKS, Sarawak - Low, Kuek Long (Bureau of Research and Consultancy (BRC), 2000)
There is a paucity of systematic research on prediction of academic achievement at the tertiary educational level for Malaysian students despite the important role that universities play in the Malaysian communities, this study is an attempt to examine the relationship between prior achievement, socio-economic background, mass media environment and academic achievement at UiTM Samarahan Campus. This study found that prior achievement, career expectation, father's educational attainment and mass media environment, in particular reading in the English Language Medium contribute positively to academic achievement. On the other hand, findings of the study suggest that there is no meaningful relationship between attending pre-commerce classes and academic achievement.